Analisis Putusan Mahkamah Agung Terhadap Perkara Wanprestasi Pembangunan Perumahan: (Studi Kasus Perkara Nomor 694/PK/Pdt/2017) - Ida Ayu Anom Tri Laksmi; Aris Munandar (Fakultas Hukum Universitas Mataram, 2023)
The aim of this research is to find out the Judge’s consideration basis in resolving the default case of house construction contracts, case number 694/PK/Pdt/2017 along with its legal consequences. Applied research method in normative-juridical and doctrinal legal research. Research result indicates that (1) The Judge’s consideration basis in resolving default case number 694/PK/Pdt/2017 are previous Judges' verdict and regulation on default; (2) Emerging legal consequences from this default case is the contract is legally voidable and appeal pleader obliged to compensate defendant’s loss, also obliged to pay for interest and trial fee.